Unusual Magnetic Behaviour of Ultrafine Stable Nickel Nanoparticles - Mondal, O. (Journal of Scientific Research, 2024)
Ultrafine nickel nanoparticles have been synthesized using a capping agent-assisted chemical reduction technique using two different reaction media – water and ethylene glycol. The effect of the capping agent and reaction medium concentration on the particle size and their magnetic properties have been extensively studied. The size of the nickel nanoparticles, as revealed from X-ray diffractograms and transmission electron micrographs, is less than 5 nm. The energy-dispersive X-ray spectrum confirms that the synthesized nanoparticles are pure nickel. No other element is present in the spectrum. The nanoparticles exhibit surface plasmon resonance in ultraviolet (⁓310 nm). The blue shift in the absorbance peak's position further confirms the particle's miniaturization. The samples should have exhibited superparamagnetic behavior because the particle size is in the nanometer range. Instead, the ferromagnetic behavior of the samples has been observed at ambient temperature, which is attributed to the formation of clusters of nanoparticles. This property makes the material applicable for data storage technology.